2004
DOI: 10.1111/j.1740-8261.2004.04032.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro prediction of canine urolith mineral composition using computed tomographic mean beam attenuation measurements

Abstract: Determination of urolith mineral composition is critical for management of urolithiasis in dogs and cats. Using computed tomography, urolith physical density, and hence chemical composition, can be quantified using mean beam attenuation measurements (Hounsfield units; HU). This study was designed to establish in vitro reference ranges for three types of compositionally pure uroliths retrieved from dogs. Sixty-six canine uroliths (22 uric acid, 21 calcium oxalate, 14 struvite, nine mixed or compound) were place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
1
4
0
6
Order By: Relevance
“…Secondary changes such as acquired porto‐caval shunts and splenomegaly can also be seen. Changes in the appearance of the liver in this gray seal were not seen, which could be explained by several reasons. First, the absence of intra‐abdominal fat prevented the clear delineation of the liver margins from other abdominal organs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Secondary changes such as acquired porto‐caval shunts and splenomegaly can also be seen. Changes in the appearance of the liver in this gray seal were not seen, which could be explained by several reasons. First, the absence of intra‐abdominal fat prevented the clear delineation of the liver margins from other abdominal organs.…”
Section: Discussionmentioning
confidence: 74%
“…However, in human medicine, CT is considered to be superior to ultrasound to detect urinary calculi . The CT appearance of different uroliths, and especially their attenuation values, have been described in vitro in dogs and in vivo in humans . In this case, CT allowed full assessment of the extent of the nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…A tomografia computadorizada (TC) têm se popularizado como melhor método no diagnóstico da litíase urinária em medicina, uma vez que apresenta 94% de sensibilidade na detecção dos cálculos, além de fornecer alternativas diagnósticas para dor lombar aguda (TÜRK et al, 2016;NYKAMP, 2017). Essa técnica permite facilmente a distinção de urólitos dos tecidos moles circundantes (PRESSLER et al, 2004). Em estudo realizado com felinos, a tomografia computadorizada foi capaz de diagnosticar cálculo ureteral em três pacientes, cujo urólitos não haviam sido observados na radiografia simples e ultrassonografia abdominal (KYLES et al, 2005).…”
Section: Tomografia Computadorizadaunclassified
“…Além da capacidade de detecção da presença de urólitos, outra aplicação do exame seria a possibilidade de predizer a composição dos cálculos com base nas diferentes densidades (PRESSLER et al, 2004;NYKAMP, 2017). A determinação da composição in vivo beneficia o tratamento médico ao facilitar a escolha terapêutica, quando não há possibilidade de remoção da pedra.…”
Section: Tomografia Computadorizadaunclassified
“…A recent human study showed that non-contrast computed tomography could be used to predict the composition of uroliths on the basis of differences in radiodensity, measured in Hounsfield units. One in vitro study of uroliths removed from dogs showed the prediction of mineral content to be 75% to 88% accurate for pure uroliths, but mixed uroliths could not be accurately assessed (Pressler et al, 2004).…”
Section: Computed Tomographymentioning
confidence: 99%